The suspect - Lescroart, John T. (Dutton, 2007)
"When Dr. Caryn Dryden is found floating dead in her hot tub, her husband becomes the prime suspect. Gina Roake takes the case and feels her client's innocence will be easy to prove since he was at his cabin on Echo Lake that weekend."--From source other than the Library of Congress